An integrated microfluidic device for two-dimensional combinatorial dilution - Jang, Yun-Ho (2011)
High-throughput preparation of multi-component solutions is an integral process in biology, chemistry and materials science for screening, diagnostics and analysis. Compact microfluidic systems enable such processing with low reagent volumes and rapid testing. Here we present a microfluidic device that incorporates two gradient generators, a tree-like generator and a new microfluidic active injection system, interfaced by intermediate solution reservoirs to generate diluted combinations of input solutions within an 8 × 8 or 10 × 10 array of isolated test chambers. Three input solutions were fed into the device, two to the tree-like gradient generator and one to pre-fill the test chamber array. The relative concentrations of these three input solutions in the test chambers completely characterized device behaviour and were controlled by the number of injection cycles and the flow rate. Device behaviour was modelled by computational fluid dynamics simulations and an approximate analytic formula. The device may be used for two-dimensional (2D) combinatorial dilution by adding two solutions in different relative concentrations to each of its three inputs. By appropriate choice of the two-component input solutions, test chamber concentrations that span any triangle in 2D concentration space may be obtained. In particular, explicit inputs are given for a coarse screening of a large region in concentration space followed by a more refined screening of a smaller region, including alternate inputs that span the same concentration region but with different distributions. The ability to probe arbitrary subspaces of concentration space and to control the distribution of discrete test points within those subspaces makes the device of potential benefit for high-throughput cell biology studies and drug screening.